Understanding Capital Sources For MSMEs In Gresik - Handayani, Anita (IJBLE Scientific Publications Community Inc., 2024)
Apart from having an important role in the nation's economy, MSMEs also have classic problems, namely related to capital. The source of capital is always a problem because MSMEs have limitations in reaching access to capital, but without realizing that there is a meaning of capital that is not interpreted by these MSMEs so that this study aims to analyse the meaning of capital sources from MSMEs in Gresik with a qualitative approach. The results showed that in running their business, many MSMEs use their own capital. Own capital is chosen because it is easier and does not pose a risk in the future and avoids formal debt because they understand the risks with formal debt when income is down, but MSME players use debt in the form of raw materials that can be used first to run a business. The meaning of this debt is what MSMEs do not realize that basically they use debt as capital in running their business.